Fatal encephalitis due to Nipah virus among pig-farmers in Malaysia - Chua, K.B.; Goh, K.J.; Wong, K.T.; Kamarulzaman, A.; Tan, P.S.K.; Ksiazek, T.G.; Zaki, S.R.; Paul, G.; Lam, S.K.; Tan, C.T. (1999)
Background Between February and April, 1999, an outbreak of viral encephalitis occurred among pig-farmers in Malaysia. We report findings for the first three patients who died. Methods Samples of tissue were taken at necropsy. Blood and cerebrospinal-fluid (CSF) samples taken before death were cultured for viruses, and tested for antibodies to viruses. Findings The three pig-farmers presented with fever, headache, and altered level of consciousness. Myoclonus was present in two patients. There were signs of brainstem dysfunction with hypertension and tachycardia. Rapid deterioration led to irreversible hypotension and death. A virus causing syncytial formation of vero cells was cultured from the CSF of two patients after 5 days; the virus stained positively with antibodies against Hendra virus by indirect immunofluorescence, IgM capture ELISA showed that all three patients had IgM antibodies in CSF against Hendra viral antigens. Necropsy showed widespread microinfarction in the central nervous system and other organs resulting from vasculitis-induced thrombosis. There was no clinical evidence of pulmonary involvement. Inclusion bodies likely to be of viral origin were noted in neurons near vasculitic blood vessels. Interpretation The causative agent was a previously undescribed paramyxovirus related to the Hendra virus. Close contact with infected pigs may be the source of the viral transmission. Clinically and epidemiologically the infection is distinct from infection by the Hendra virus. We propose that this Hendra-like virus was the cause of the outbreak of encephalitis in Malaysia.